Adaptive co-management: A novel approach to tourism destination governance?. (December 2018) - Islam, Md. Wasiul; Ruhanen, Lisa; Ritchie, Brent W.
Abstract: Although tourism destination governance has been a subject of academic enquiry for some time now, in practice, governance is still a challenge for many tourism destinations around the world. Adaptive co-management (ACM) is a dynamic approach to governance whereby institutional arrangements and ecological knowledge are continually revised through a process of 'learning-by-doing'. Founded on the active participation and collaboration of diverse stakeholder groups, ACM has been used extensively in the governance of natural resource contexts and so may offer valuable synergies for tourism governance; particularly the governance of tourism in protected areas. This review paper presents a critical review and synthesis of the ACM literature, identifying synergies and opportunities for enhancing tourism governance practices in protected area contexts through an ACM approach. A conceptual framework is developed from the review that identifies principles, stages, variables and expected outcomes of the ACM approach. Future research directions for ACM in tourism are proposed that incorporate governance, social learning and multi-stakeholder engagement.